Effects of Diet on the Rumen and Blood Volatile Fatty Acid Concentrations of Growing Calves - Ogundola, F. I. (Faculty of Agriculture, University of Ife, 2015)
Twenty-four calves belonging to the White FuIani (WF) Friesian and German Brown (GB) breeds were used to evaluate the effects of milk based diets, on rumen fermentation pattern and blood volatile fatty acid concentrations. The calves were assigned randomly to four diets as they became available at the age of 4 days, and fed their respective diets for 84 days. The diets were: 1. milk fed twice daily plus a concentrate and grass supplement (TMCG). 2. milk fed twice daily plus a concentrate supplement (TMC). 3. milk fed once daily plus a concentrate and grass supplement (OMCG). 4. milk fed once daily plus a concentrate supplment (OMC). Rumen and blood samples were taken on the last 3 days of the 4th, 8th and 12th week of the experiment for the measurement of rumen pH, rumen and blood volatile fatty acid (VFA) concentrations. Significant age, breed and dietary effects were observed on rumen and plasma volatile fatty acids concentrations but not on rumen pH. Friesian and GB calves had higher total rumen VFA than WF calves (3.3, 3.1 and 2.4 meg/100ml respectively) and plasma VFA concentration followed a similar pattern. Both plasma and rumen total VFA increased (P < .01) with age, and grass supplemented calves tended to have higher VFA concentrations. Significant positive correlations were observed between rumen and plasma VFA concentrations, while significant negative correlations were observed between rumen pH and VFA concentrations.